Effects of Dietary Fatty Acid Saturation on Broiler Chickens Subjected to High Ambient Temperatures - Nwe, Nwe Htin (2005)
The effects of dietary fat with various fatty acid saturations on physiological response, performance, carcass fatty acid deposition, and immune response and disease resistance in heat stressed broiler chicks were studied. Day old male broilers chicks (Cobb) were brooded and consequently maintained at 24 * 1°C in an environmentally controlled house. All the chicks were fed a starter ration without added fat. On day 2 1 onwards, equal numbers of chicks were provided isocaloric and isonitrogenous finisher diets containing different oil sources namely 8% menhaden fish oil (FO), 8% soybean oil (SO), 8% coconut oil (CO), 8% palm oil (PO) or no added fat (control). From day 28 to 41, all birds were exposed to 36 k 1°C for 2 hlday. Following 14 days of the heat challenge, the PO birds had greater body weights than the other three groups. The control and PO birds were less hyperthermic and had smaller increases in heterophiVlymphocyte ratio than those provided FO, SO and CO diets. Although the mortality rate of PO birds was higher than the control, it was lower than their FO, SO and CO counterparts. Diets rich in saturated fatty acids (CO) increased abdominal fat and crude fat per cent of thigh meat as compared to diets rich in polyunsaturated fatty acids (SO and FO). Tissue fatty acid deposition was significantly different according to dietary oil sources, specific to tissue type, fatty acid structure, and the amount of deposition was not proportional to its intake. Broilers fed 8% fish oil showed higher concentration of long-chain n-3 PUFA (EPA and DHA) in the meat tissue than other counterparts. High inclusion levels of dietary PUFA could provide the recommended polyunsaturated to saturated fatty acid ratio in meat tissue of broilers under high ambient temperatures. Broiler chicks (Cobb) were used to study dietary self-selection of fat under high ambient temperatures. Commencing from day 21, chicks were assigned to one of four dietary treatments: (1) diet with 8% palm oil (PO); (2) diet with 8% soybean oil (SO); (3) diet without added fat (control); and (4) a choice of PO, SO and control (CH). From day 28 to 41, all birds were exposed to 34 * 1°C continuously. High addition of palm oil but not soybean oil improved survivability and reduced senun creatine kinase levels of broiler chickens during heat exposure. On day 41, the body weights of PO, SO and CH birds were greater than controls. Although the intake of control, PO and SO diets was similar during heat exposure, the CH birds had a lower creatine kinase activity and mortality rate than those provided SO diet but not significantly different fkom those fed control and PO diets. It was concluded that a high addition of palm oil but not soybean oil is beneficial to heat-stressed broiler chickens. Selfselection of high fat diet can allow birds to match their physiological requirement under heat stress conditions. The effects of dietary a-linolenic and linoleic fatty acid on disease resistance and immune response of heat-stressed broiler chicks (Cobb) were investigated. From day 21 onwards, broiler chicks were fed isocaloric and isonitrogenous finisher diets containing either 8% palm oil (neither rich in linolenic or linoleic acid), 8% soybean oil (rich in linoleic acid) and 8% flaxseed oil (rich in linolenic acid). All birds were vaccinated against Newcastle disease on day 7 and 21. From day . . - . . - - 36 to 50, equal numbers of birds fkom each dietary group were exposed to 38 * t°C and 80% relative humidity for 2 hiday. The remaining birds were maintained under 24 * 1 "C. Feed and water were not provided throughout the heat challenge period. On day 37, all chicks were intranasally challenged with an infectious bursal disease vaccine, V877 strain (Malaysia Vaccine and Pharmaceuticals Sdn Bhd, Kuala Lumpur, Malaysia). Bursal samples were taken for histopathological examination, determination of viral RNA and fatty acid analysis. Significantly less viral replications were detected in both heated and non-heated broiler chicks fed did containing 8% flaxseed oil on day 7 post infection. Broiler chicks fed 8% palm oil showed significantly higher viral replications on day 7 post infection under both lower and higher ambient temperatures. Mortality, hetemphil/lymphocyte ratio, antibody production and bursal lesion scores were not significantly affected which suggests that palm oil may enhance tolerance to infectious bursal disease under both ambient temperatures.